Theoretical Frameworks of Leadership in Nursing: Critical Reflections - Charalambous, Andreas (My University, 2023)
The objective of this article is to present a comprehensive view on the topic of nursing leadership discussing the theoretical frameworks that underpin its manifestation, the leadership styles in nursing, the overall landscape in nursing leadership including the context where leadership is being practiced, and finally looking at the educational pathways for building leadership capacity and sustainability DATA SOURCES: Relevant studies on the topic as well professional associations, national and international organizations' evidence have formed the basis for this article.
Keywords: Archetypes; Competency; Frameworks; Leadership; Transformational leadership